2022
DOI: 10.1108/jeee-04-2022-0115
|View full text |Cite
|
Sign up to set email alerts
|

Female entrepreneurship in emerging and developing countries: a systematic review of practical and policy implications and suggestions for new studies

Abstract: Purpose Women entrepreneurs face several challenges in creating and running ventures, especially in emerging and developing countries. In this sense, by aiming to generate inputs capable of helping overcome them, this study aims to categorize the policy, managerial and practical implications of articles whose empirical research was in one or more of the 155 emerging and developing countries. Further, although scholars have addressed female entrepreneurship in developed economies, there is scant literature in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 105 publications
0
4
0
Order By: Relevance
“…While women’s entrepreneurship is no doubt of global importance (Brush and Cooper, 2012), its growth and relevance is to the world’s emerging economies is of particular significance (Anderson and Ojediran, 2022; Corrêa et al , 2022). Representing an undeveloped potential for future economic growth and development in emerging economies (Kimbu and Ngoasong, 2016), women’s entrepreneurship in emerging economies remain largely under-researched and under-theorised by the existing literature (Ahl, 2006; Rosca et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While women’s entrepreneurship is no doubt of global importance (Brush and Cooper, 2012), its growth and relevance is to the world’s emerging economies is of particular significance (Anderson and Ojediran, 2022; Corrêa et al , 2022). Representing an undeveloped potential for future economic growth and development in emerging economies (Kimbu and Ngoasong, 2016), women’s entrepreneurship in emerging economies remain largely under-researched and under-theorised by the existing literature (Ahl, 2006; Rosca et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The second issue faced in the literature is lack of gendered contextualisation of women’s entrepreneurship in emerging economies (Mustafa and Treanor, 2022). While existing research has recognised differences between developed and emerging economies (Chan and Mustafa, 2021; Hoskisson et al , 2000), significant differences can also be observed among emerging economies with respect to not only rates of women’s entrepreneurship (Corrêa et al , 2022), but also the range of socio-economic and cultural factors which shape such entrepreneurial activity. One region which consists of a diverse range of economic, social, political, cultural and religious differences is Asia.…”
Section: Introductionmentioning
confidence: 99%
“…Micro, small and medium enterprises (MSMEs) are widely regarded as a nation's economic engine and is viewed as a means for women's empowerment, especially in the context of Necessity and opportunity entrepreneurs 159 emerging economies. To advance women entrepreneurship in developing countries, alignment and integration with government policies are considered vital (Corrêa et al, 2022). According to the Annual Report of the Ministry of Micro, Small and Medium Enterprises 2021-2022, in India, there are approximately 63.39 million units and only about 20.37% are owned by women.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have analyzed their entrepreneurship attributes, such as business competence, performance, and entrepreneurial orientation, with the purpose of helping them to recognize the most appropriate aspects of their performance and driving factors, as well as motivation (Corrêa et al 2021). Other studies have focused on mapping and categorizing implications referring to their policy, managerial, and practical aspects, with the aim to raise awareness of the policies to be undertaken on overcoming their entrepreneurial challenges (Corrêa et al 2022). However, "every region has its own social and cultural challenges affecting differently to women entrepreneurs" (Rashid and Ratten 2020, p. 37).…”
Section: Introductionmentioning
confidence: 99%